2020
DOI: 10.1186/s13047-020-00410-2
|View full text |Cite
|
Sign up to set email alerts
|

Plantar pressure sensors indicate women to have a significantly higher peak pressure on the hallux, toes, forefoot, and medial of the foot compared to men

Abstract: Background: Sex-related differences of plantar pressure distribution during activities should be thoroughly inspected as it can help establish treatment and prevention strategies for foot and ankle problems. In-shoe measurement systems are preferable without space and activity restrictions; however, previously reported systems are still heavy and bulky and induce unnatural movement. Therefore, a slim and light plantar pressure sensor was newly developed to detect the effect of sex difference on plantar pressur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Although this study did not include cases of hallux valgus (HV), females had a higher load of the hallux than males. Studies reported a meta-analysis that estimated that female HV prevalence (30%) was 2.3 times greater than that in males (13%) [ 21 ]. Although many studies cannot reach a unified conclusion, there was no denying that gender differences in plantar mechanical parameters may be one of the reasons for the increase in hallux valgus in females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this study did not include cases of hallux valgus (HV), females had a higher load of the hallux than males. Studies reported a meta-analysis that estimated that female HV prevalence (30%) was 2.3 times greater than that in males (13%) [ 21 ]. Although many studies cannot reach a unified conclusion, there was no denying that gender differences in plantar mechanical parameters may be one of the reasons for the increase in hallux valgus in females.…”
Section: Discussionmentioning
confidence: 99%
“…Males and females have different bone structures and muscle strength, and studies have shown that females are more likely than males to sustain lower limb injuries while running [ 21 , 22 ]. Females are more prone than males to have ligamentous laxity of the ankle joint, and females are approximately twice as likely as males to have ankle sprains [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“… Summary of typical algorithms used for processing data acquired by low-cost sensors including LR [ 20 ], DT [ 21 ], FFT [ 22 ], SVM [ 22 ], NB [ 23 ], SA [ 29 ], WT [ 34 ], LDA [ 40 ], ANN [ 42 ], HMM [ 56 ] and KNN [ 65 ]. …”
Section: Figurementioning
confidence: 99%
“…Most insole-based systems reported in the literature were tested on a small group of individuals of same gender, ethnicity and/or age. This poses a problem as individuals of different genders and ethnicities are known to have different in foot morphologies [174,175]. As a result, a standard placement of sensors may not be suitable for all users of the device.…”
Section: E System Validationmentioning
confidence: 99%